2013
DOI: 10.1016/j.polymer.2012.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature organic ferromagnetism in the crystalline poly(3-hexylthiophene): Phenyl-C61-butyric acid methyl ester blend film

Abstract: "Roomtemperature organic ferromagnetism in the crystalline poly(3-hexylthiophene): Phenyl-C61-butyric acid methyl ester blend film"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
4
7
0
Order By: Relevance
“…Both polymer conjugation and delocalization was affected by the electron transfer. Similar results were reported by B. Yang et al They observed that the saturation ferromagnetism of polymer P3HT mixed with phenyl-C61-butryic acid methyl ester (PCBM) was about 0.65 emu/g and suggested that the ferromagnetism origin is associated with P3HT crystallization and the charge transfer between P3HT and PCBM [29]. Accordingly, this study indicated that the magnetism of polymer composite could be further tuned by adjusting the content of each component, and also the interaction at the interface.…”
Section: Resultssupporting
confidence: 84%
“…Both polymer conjugation and delocalization was affected by the electron transfer. Similar results were reported by B. Yang et al They observed that the saturation ferromagnetism of polymer P3HT mixed with phenyl-C61-butryic acid methyl ester (PCBM) was about 0.65 emu/g and suggested that the ferromagnetism origin is associated with P3HT crystallization and the charge transfer between P3HT and PCBM [29]. Accordingly, this study indicated that the magnetism of polymer composite could be further tuned by adjusting the content of each component, and also the interaction at the interface.…”
Section: Resultssupporting
confidence: 84%
“…Such compounds often exhibit interesting magnetic properties, which underlie spintronic elements and quantum devices . Although single molecule magnets were found to show ferromagnetism only at low temperatures, some organic molecular crystals (which may be chiral , ), as well as some paramagnetic and diamagnetic organic molecules assembled in supramolecular structures, , reveal ambient temperature ferromagnetism. For example, the assembly of hexacyanoferrate­(III) anions and nickel­(II) bisdiamino complexes of the chiral ligand trans -cyclohexane-1,2-diamine yields cyanide-bridged two-dimensional ferromagnets. Their crystal structure is built from cyanide-bridged bimetallic planes separated by bulky ligands.…”
mentioning
confidence: 99%
“…% P3HT sample had more pronounced P3HT absorption peaks and shoulders, distinctly indicating higher degree of crystallinity in the P3HT polymer domains. [21][22][23] In addition, the absorption peak of the 50 wt. % P3HT film was at about 496 nm, which exhibited an evident red-shift of about 25 nm compared to that of the 25 wt.…”
mentioning
confidence: 99%